Hepatic Kaposi Sarcoma after Kidney Transplantation: A Case Report - Seunghyeon Roh; Myoung Seok Lee; Siwon Jang; Min Hoan Moon; Joon Koo Han (Journal of the Korean Society of Radiology)
Kaposi sarcoma is an undisputed malignancy associated with a heightened relative risk after transplantation. Similar to other causes of Kaposi’s sarcoma, cutaneous involvement is typical in post-transplant patients; however, visceral involvement rarely occurs. We report a rare case of de novo hepatic Kaposi’s sarcoma manifesting as an ill-defined infiltrative lesion in the left lobe of the liver in a patient who was immunosuppressed for 9 months after a kidney transplantation using ultrasonography, CT, MRI, and fluorodeoxyglucose-PET.